Bioremediation of Textile Industrial Effluents Using Nutraceutical Industrial Spent - Taqui, Syed Noeman (2022)
Funding Information: The authors extend their appreciation to the Deanship of Scientific Research at King Khalid University (KKU) for funding this research through the Research Group Program under the Grant Number: R.G.P.2/248/43. Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.